A review of the halal status of ceramide in cosmetics: a strategic approach to halal policy and consumer awareness in Indonesia - Basuki, Nazih; Yulianti, Rista; Fathurrohman SW, Oman; Salamah, Nina (Journal of Halal Product and Research (JHPR), 2025)
In cosmetics, ceramide plays a significant role in maintaining healthy skin. However, ensuring its halal status remains challenging because ceramide can be sourced from animals, plants, microbial fermentation, or chemical synthesis, each presenting its own halal-critical points. With the growing demand for halal cosmetics in Indonesia and mandatory halal certification for raw materials and finished products, special attention is required to maintain consumer trust. This study employed a literature review by analyzing registration data of ceramide-based cosmetic products from the Indonesian Food and Drug Authority (BPOM) and halal certification data from the Halal Product Assurance Organizing Agency (BPJPH). The review aimed to identify compliance gaps, examine halal policies, and understand the critical halal points in ceramide production. The analysis shows 74.52% of ceramide-based cosmetic products registered with BPOM do not have halal certification. Regulatory factors, consumer awareness, and halal raw material supply chain constraints influence this shortfall. Ceramide derived from animal sources poses the greatest challenge, whereas microbial fermentation and chemical synthesis offer greater potential for halal compliance if properly supervised. Collaboration among BPJPH, BPOM, and the Ministry of Trade is crucial to ensure compliance. Moreover, mandatory halal requirements on raw materials before the final product stage are essential to guarantee comprehensive halal assurance. Institutional synergy, public education, and improved access to halal raw materials are strategic measures to support Indonesia’s halal cosmetics industry. This study provides strategic guidance for regulators and industry players in addressing challenges related to halal regulations for ceramide-based cosmetics.   Keywords: Ceramide, Halal Cosmetics, Halal Mandatory, Halal Certification, Halal Critical Point